Gambaran Pengetahuan dan Sikap Pasien Post Bedah Elektif tentang Informed Consent di RS X Tahun 2024 - Nurfadhilatussifah, Dela; Sugiarti, Ida (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2024)
Informed consent is giving consent after obtaining complete information. The patient has the right to accept or reject some or all of the assistance measures that will be provided. This decision depends on the patient's knowledge and attitude regarding consent to medical treatment. Several cases of medical malpractice in Indonesia actually started with the failure to implement informed consent properly. The aim of this research is to analyze the knowledge and attitudes of post-elective surgery patients regarding informed consent at Hospital X. This type of research is descriptive quantitative. The sampling technique uses accidental sampling. The population in this study was 42 patients after elective surgery in December 2023. The research instrument used a questionnaire sheet. The results of the study showed that of the 42 post-elective surgical patients regarding informed consent at Hospital Efforts are needed to simplify explanations in language that is easy for patients to understand and use certain media to improve patient understanding.